Role of the atherogenic index of plasma in the association of combined healthy lifestyles with kidney stones: a cross-sectional study using data from the US National Health and Nutrition Examination Survey - Jun Wang; Dawei Wang; Guoliang Lu; Jinjun Tian; Ding-Guo Zhang (BMJ Open)
Objective Kidney stones (KS) are a growing global health concern with significant morbidity. Although individual lifestyle factors have been linked to KS risk, the combined influence of healthy lifestyles and the mediating role of lipid metabolism remains unclear. This study aimed to investigate whether the atherogenic index of plasma (AIP) mediates the link between KS risk and a composite healthy lifestyle score.Design Cross-sectional study.Setting National Health and Nutrition Examination Survey (NHANES) 2007–2016, USA.Participants 7576 US adults (mean age, 47.39 years; 52.57% male).Outcome measures The association between healthy lifestyle scores and KS risk was assessed by multivariable logistic regression. The mediating role of AIP was evaluated through mediation analysis. Dose–response relationships were examined by restricted cubic spline (RCS) analysis. Stratified analyses explored potential effect modifications by age, sex, race/ethnicity and metabolic conditions.Results Participants in the highest healthy lifestyle score quartile had 0.49 times the odds of KS compared with individuals in the lowest quartile (OR, 0.49; 95% CI, 0.38 to 0.64). A 19% decreased risk of KS was linked to every unit rise in the healthy lifestyle score (OR, 0.81; 95% CI, 0.76 to 0.87). An inverse linear dose–response association was shown by RCS analysis between healthy lifestyle scores and KS risk (P-overall<0.001, P-nonlinearity=0.321). AIP mediated 7.18% (95% CI, 1.07% to 14.40%) of the association between lifestyle and KS. The association remained across sensitivity analyses and subgroups.Conclusions A healthier lifestyle is linked to lower odds of KS, with AIP partially mediating this association. These results emphasise the potential importance of composite lifestyle modifications for the prevention of KS.